The correlation between primary dysmenorrhea and oxidative stress markers in adolescents - Laleli, Bergen; Timur, Burcu (The European Research Journal, 2022)
Objectives: Primary dysmenorrhea is the most common gynecological complaint in adolescent girls. Among many factors, oxidative stress (OS) is thought to be a potential factor in the etiology of primary dysmenorrhea. In this study, it is thought that the use of IMA, thiol, and disulfide levels as a diagnostic marker in primary dysmenorrhea and antioxidant interventions may play a role in the treatment of primary dysmenorrhea and may benefit the pathophysiological and treatment process of the disease. Methods: Thirty adolescent girls (study group) with grade 2.3 primary dysmenorrhea who applied to outpatient clinic and 30 healthy young girls (control group) of similar age group were included in the study. Primary dysmenorrhea grade was analyzed with the help of the visual analog scale (VAS) and verbal multidimensional scoring system (VMS). Patient`s basal hormone levels in the early follicular phase, serum albumin, IMA, total thiol, native thiol, disulfide, C-reactive protein (CRP), and cancer antigen-125 (CA-125) were recorded as main parameters. Results: Oxidative stress markers were compared between the primary dysmenorrhea and control groups. Although albumin, IMA, and disulfide levels were higher on average in the group with dysmenorrhea, the difference was not statistically significant. Disulfide level was found to be significantly higher in the group with CA125 ≥ 35. Conclusions: In our study, we examined serum albumin, IMA, total thiol, native thiol and disulfide levels in two groups resuts were not statistically significant. In this study, we concluded that as the CA125 level increased, the disulfide level increased in parallel.